EDUCATIONAL DISADVANTAGES OF YOUNG TURKISH IMMIGRANTS IN GERMANY - Sayime ERBEN KEÇİCİ (Fırat University, 2019)
The object of this study is to testify that the educational failure of unsuccessful young Turks who live in Germany is not only those young people themselves or their parents (i.e. cultural and family background) but also the radical conditions in the application of German educational system. It is possible to show how an educational period proceeds and how young Turkish immigrants are canalized to certain positions both during educational period and in employment market after educational period by making qualitative-oriented interviews with them. It is observed that the ethnogenesis affects the situation as a disparity characteristic and so it is decided who will be socially marginalized or not as per ethnic origin. It is also observed that the denied support and stimulation of teachers and the negative behaviors of employers impact those young people negatively. Nearly all young people who are interviewed mentioned that they were exposed to unequal behaviors’ of teachers during their educational period and unequal attitudes of employers both during their practical training and at their job. On the other hand, it is also observed that potential of a young is limited in some aspects and he/she is negatively affected since the Turkish parents have insufficient knowledge about German Educational System.